Understanding the moisture sensitivity of warm-mix asphalt binders based on bond strength. Issue 1 (10th February 2023) - Sukhija, Mayank; Saboo, Nikhil; Pani, Agnivesh
Abstract : Moisture damage in asphalt mixtures is typically attributed to the loss of bond strength at the interface of the asphalt binder and aggregate matrix. Selecting an appropriate combination of materials that resist moisture-induced damage is therefore critical. This concern is of utmost importance when asphalt mixtures are prepared at lower temperatures (i.e. warm-mix asphalt (WMA) mixtures). An attempt was thus made to quantify the impact of moisture on asphalt mixtures prepared using four different WMA additives and two aggregates through bond strength tests. The results showed that WMA binders imparted similar or even higher bond strength than the base asphalt binder, regardless of the aggregate source and moisture exposure (wet or dry). The use of WMA additives improved the moisture sensitivity (evaluated through the bond strength ratio), despite lower production temperatures, compared with the base asphalt binder (VG30). Statistical analysis showed that the asphalt binder type significantly affected the bonding mechanism and moisture sensitivity. Based on the ranking protocol used in this study, use of the chemical-based WMA additive Rediset showed the best performance compared with other WMA additives in VG30.